2020
DOI: 10.1136/bmjhci-2020-100140
|View full text |Cite
|
Sign up to set email alerts
|

Time to listen: a mixed-method study examining community-based views of mobile technology for interventions to promote physical activity

Abstract: IntroductionA mixed-method, co-design approach to studying the adoption of mobile health (mHealth) technology among African-American (AA) women has not been fully explored. Qualitative data may contextualise existing knowledge surrounding perceptions of mHealth among AA women as part of formative work for designing a physical activity application (app).MethodsA convenience sample of 16 AA women completed an informatics survey prior to participating in focus groups exploring their use of mobile technology and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 46 publications
0
39
0
Order By: Relevance
“…The studies included in this review showed mixed support for IPT 2, which focuses on how users’ education, literacy, and digital skills might impact their engagement with and use of DHIs. For example, some studies recognized the impact of low digital literacy and skills on successful engagement with DHIs in participants from both African-American and South Asian backgrounds [ 52 , 54 , 61 , 62 ]. Both Claudel et al [ 54 ], 2020, and Dick et al [ 61 ], 2011, reported that app design and user interface are aspects that might act as potential barriers for users with low digital literacy.…”
Section: Resultsmentioning
confidence: 99%
“…The studies included in this review showed mixed support for IPT 2, which focuses on how users’ education, literacy, and digital skills might impact their engagement with and use of DHIs. For example, some studies recognized the impact of low digital literacy and skills on successful engagement with DHIs in participants from both African-American and South Asian backgrounds [ 52 , 54 , 61 , 62 ]. Both Claudel et al [ 54 ], 2020, and Dick et al [ 61 ], 2011, reported that app design and user interface are aspects that might act as potential barriers for users with low digital literacy.…”
Section: Resultsmentioning
confidence: 99%
“…Before this pilot study, we conducted the DC CV Health and Needs Assessment (DC-CHNA) study (NCT019227783) to investigate bio-psychosocial and neighborhood conditions resulting in poor CV health. The objective of the previous work was to determine ways to use mobile health technology to promote CV health for populations in lower SES DC Wards 5, 7, and 8 [40][41][42][43][44]. First, the DC-CHNA created a community advisory board, the DC Cardiovascular Health and Obesity Collaborative (DC-CHOC), to give feedback on developing and implementing the DC-CHNA and subsequent community-based projects.…”
Section: Preliminary Studymentioning
confidence: 99%
“…First, the DC-CHNA created a community advisory board, the DC Cardiovascular Health and Obesity Collaborative (DC-CHOC), to give feedback on developing and implementing the DC-CHNA and subsequent community-based projects. The DC-CHOC consists of representatives from the DC faith-based community, US government agencies, academia, and health advocacy organizations, all of whom are devoted to addressing obesity and CV health in at-risk DC communities [44][45][46][47]. In this study, 11 participants from DC-CHNA were asked to carry GPS units and use the EMA app and then test the feasibility of both a GPS device and an EMA app for African American women.…”
Section: Preliminary Studymentioning
confidence: 99%
“…Participation from racial and ethnic minorities in clinical trials has been burdened by issues surrounding mistrust and access to healthcare, both of which ultimately impact referral to clinical trials. 7 8 Furthermore, participation barriers may extend beyond these recognised factors. To address barriers, community-based participatory research (CBPR) has emerged to involve communities at all stages of a research study life cycle from study design through dissemination of results.…”
Section: Introductionmentioning
confidence: 99%
“…Participation from racial and ethnic minorities in clinical trials has been burdened by issues surrounding mistrust and access to healthcare, both of which ultimately impact referral to clinical trials 7 8. Furthermore, participation barriers may extend beyond these recognised factors.…”
Section: Introductionmentioning
confidence: 99%